A practical model of faculty development in medical education: Make it accessible, versatile, and easy to use! - Moon, Henry; D’Eon, Marcel (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Implication StatementFaculty development programs should provide transformative resources and prioritize the unique needs of faculty. However, if faculty members face difficulty in accessing these programs, the potential impact of the valuable resources may be limited. To alleviate this issue, we designed a faculty development program that is available to anyone at any time and in any configuration. By allowing faculty to choose from a diverse range of medical education topics, they may promptly apply crucial concepts in their teaching and education leadership roles. This program allows faculty members to engage in personalized professional development, enhance their teaching practices, and foster professional growth. Also, program coordinators and administrators can seamlessly integrate our resources into their existing faculty development program. These resources can serve as self-study materials, supplements for existing programs, or a stand-alone curriculum with high accessibility, versatility, and ease of use.